PERINCIPAL POLICY ANALYISIS IN PROVIDING QUALITY EDUCATION AT TIRTAYASA INTEGRATED ISLAMIC ELEMENTARY SCHOOL OF SERANG CITY - Pribadi, Reksa Adya; Wahyuni, Dwi (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2019)
Abstract: Teachers' performance is very determined by the policies made by the principal, the formulation of policies are made by the principal must be clear and transparent, the division of task and responsibility to teachers wisely, and measurably. The Principal's Policies in Providing of Quality Education. This study used method of qualitative descriptive. Data collection technique, interview, observation, and documentation. Principal's research subject. The result of the study included the principal understood of the main task its function and obligation to carry out quality education, the ability of principal in making policies and performing it had been clear, especially when the research subject performed supervision activities, and the results of policy that had been made to support quality education impacted to A accreditation that owned by SDIT Tirtayasa Serang. The conclusion of several policies that had been made by the Principal of SDIT Tirtayasa Serang were sufficient enough to describe quality education not only proven by accreditation that was already A, but also towards behavior and cultural habits that could make the morals of school residents to be better Keywords: Policy, Pricipal, quality Education